Work Relative Value Units Generated by Pediatric Urologists. Issue 1 (January 2016) - Kogan, Barry A.; Ritchey, Michael; Feustel, Paul
Abstract : Introduction: : As more physicians are employed by health care organizations and hospitals, salaries are often linked to productivity. To our knowledge there are no published data on RVUs (relative value units) generated by the average pediatric urologist. We sought to determine the typical work load of a pediatric urologist. Methods: : We reviewed de‐identified billing logs submitted during 2007 and 2008 to the American Board of Urology by 230 applicants for a subspecialty certificate in pediatric urology. We analyzed wRVUs (work load RVUs), including wRVUs generated by nurse practitioners/physician assistants billing incident to the physician, for evaluation and management, ultrasound, urodynamic, biofeedback and operative codes. The relationship of wRVUs to self‐reported information on practice demographics was examined. Results: : The median was 8, 156 wRVUs per year with the majority (4, 756) generated from operative procedures and the next largest amount (2, 551) generated from evaluation and management codes for office visits. The 202 men generated more wRVUs than the 28 women (median 8, 303 vs 6, 705 wRVUs, p <0.02). The 104 private practitioners generated more than the 108 academicians (median 9, 359 vs 7, 443 wRVUs, p <0.005). There was also a difference by experience. The median for 75 physicians with less than 10 years in practice vs 60 with 10 to 20 years vs 95 with more than 20 years was 7, 027 vs 8, 972 vs 8, 291 wRVUs (p <0.001). The median was similar in 145 physicians in metropolitan areas and 77 in nonmetropolitan areas (8, 279 vs 7, 410 wRVUs, p = 0.30). Conclusions: : Pediatric urologists generated an average of 8, 156 wRVUs per year. Most wRVUs are generated from operative procedures. Women and academic practitioners had lower median wRVUs. The most productive pediatric urologists were in practice between 10 and 20 years.